Ендодонтичне лікування у собак - Білий, Дмитро Дмитрович; Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Bilyi, D.; Belyi, D. D.; Bilyi, Dmytro; Bily, Dmytro; et al. (Одеський ДАУ, 2025)
станні роки характеризуються збільшенням поголів’я собак, серед яких значну частку порід складають сприйнятливі до стоматологічної патології (насамперед, собаки карликових і дрібних порід). Водночас, підвищуються вимоги до рівня надання стоматологічної допомоги, що слугує підґрунтям для підвищення ефективності лікування зубної патології. Найменш вивченою залишається ендодонтичне лікування «незрілих» постійних зубів. Наявна в публікаціях інформація свідчить про інтенсивні пошуки вирішення проблеми в двох напрямках: удосконалення адаптованих із гуманної медицини хірургічних технік та оцінка клінічних можливостей використання фармакологічних засобів в для купування запального процесу, асептизації і знеболювання та стоматологічних матеріалів для заповнення каналів і реконструкції зубів. Представлена в опублікованих рукописах інформація багатовекторна, часто стосується опису окремих клінічних випадків або кількість досліджених тварин не перевищує п’ять особин, що недостатньо для обґрунтованих заключень. Найбільш поширеним варіантом лікування є комбінація гутаперчі та силеру (за допомогою силеру забезпечують герметизацію, гутаперчі –заповнення порожнини зубного каналу), матеріал на основі мінерального триоксиду(ProRoot White MTA, RetroMTA, Quick-Set). Потенційно перспективним напрямком у ветеринарній стоматології є використання плазми і фібрину, збагачених тромбоцитами. Оцінка результатів ендодонтичного лікування базується на результатах гістологічного дослідження, визначення біологічної сумісності (матеріал/кістка), герметичності, інтенсивності запалення (у динаміці). Наразі відсутня інформаційна база, яка об’єднує дані щодо ефективності лікування собак із хворобами зубів і пародонту, що є одним із стримуючих факторів розвитку стоматології дрібних домашніх тварин. Проведений аналіз засвідчив актуальність клінічних і наукових досліджень у сфері ветеринарної стоматології. Recent years have been characterized by an increase in the number of dogs, among which a significant proportion of breeds are susceptible to dental pathology (primarily dwarf and small breed dogs). At the same time, the requirements for the level of dental care are increasing, which serves as the basis for increasing the effectiveness of the treatment of dental pathology. The least studied remains the endodontic treatment of "immature" permanent teeth. The information available in the publications indicates an intensive search for a solution to the problem in two directions: improvement of surgical techniques adapted from humane medicine and assessment of the clinical possibilities of using pharmacological agents for the purchase of the inflammatory process, asepsis and anesthesia and dental materials for filling canals and tooth reconstruction. The information presented in published manuscripts is multi-vector, often concerns the description of individual clinical cases or the number of animals studied does not exceed five individuals, which is insufficient for substantiated conclusions. The most common treatment option is a combination of gutta-percha and sealer (sealer provides sealing, gutta-percha - filling the cavity of the dental canal), a material based on mineral trioxide (ProRoot White MTA, RetroMTA, Quick-Set). A potentially promising direction in veterinary dentistry is the use of platelet-rich plasma and fibrin. The assessment of the results of endodontic treatment is based on the results of histological examination, determination of biological compatibility (material/bone), tightness, intensity of inflammation (in dynamics). Currently, there is no information base that combines data on the effectiveness of treating dogs with dental and periodontal diseases, which is one of the restraining factors in the development of small animal dentistry. The analysis demonstrated the relevance of clinical and scientific research in the field of veterinary dentistry.
Endodontic treatment in dogs
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384 Скляров Павло Миколайович https://orcid.org/0000-0002-4379-9583 Масюк Дмитро Миколайович https://orcid.org/0000-0002-2800-2580 Самойлюк Вячеслав Володимирович https://orcid.org/0000-0001-8400-8904 Вакулик Вячеслав Володимирович https://orcid.org/0000-0001-8773-2287 Лєщова Марина Олексіївна http://orcid.org/0000-0002-4251-4152
Keywords: рентгенодіагностика; X-ray diagnostics; собаки; dogs; стоматологічні захворювання; dental diseases; запалення; inflammation; лікування кореневих каналів; root canals; пульпіт; pulpitis; пародонтит; periodontitis; лікування; treatment; пломби; fillings; стоматологічні матеріали; dental materials; гістологія; histology